THE CLINICAL SIGNIFICANCE OF MATRIX METALLOPROTEINASES IN RHEUMATOID ARTHRITIS PATIENTS (REVIEW OF THE LITERATURE AND OUR OWN DATA) - Anastasiya S Avdeeva; E N Aleksandrova; E L Nasonov (Научно-практическая ревматология, 2014)
Matrix metalloproteinases (MMPs) are a group of over 20 proteolytic enzymes responsible for cleavage of protein components of the extracellular matrix. Three types of MMPs play an important role in the development of joint damage in patients with rheumatoid arthritis (RA): collagenases (MMP1, 8 and 13), stromelysins (MMP3), and gelatinases (MMP9). MMP3 is considered to be one of the key mediators of joint damage. Increased serum level of MMP is not specific for RA and may be registered in other rheumatic diseases (osteoarthritis, psoriatic arthritis, gout, ankylosing spondylitis, systemic lupus erythematosus); however, monitoring of the level of MMP is of particular clinical importance in patients with RA. MMP3 serum level may be a useful marker of disease activity. Several studies have shown a correlation of MMP3 concentration with clinical and laboratorial parameters of inflammatory activity (ESR and C-reactive protein – CRP) in RA patients. The elevated level of MMP3 is associated with radiological changes in joints and can also be a predictor of severe destructive lesions in RA patients. Evaluation of the MMP3 level can also be useful for monitoring the therapy effectiveness using both standard disease-modifying antirheumatic drugs (DMARDs) and genetically engineered biological drugs (GEBD). Thus, evaluation of MMP3 concentration is useful for assessing disease activity and efficacy of treatment with DMARDs and GEBD, as well as for predicting the severity of destructive changes in joints.